Christian ethics and secularisation: Business as usual? - Dawid E. de Villiers (Verbum et Ecclesia, 2018)
It is now 49 years since Johan Heyns’s Sterwende Christendom? [Dying Christendom] was published (1969) in which he traced the history of secularisation and its impact on the theology of his time and 36 years since the publication (1982) of the first volume of his Teologiese etiek [Theological ethics] in which he discussed the impact of secularisation on ethics. In this article, the topic of the impact of secularisation on Christian ethics is revisited. Account is taken of research conducted on the secularising impact of modernisation since then. Although empirical research points to the fact that it is not true that modernisation inevitably leads to the complete demise of religious faith and ethics, and also not that there is today absolutely no room for religious influences in the different social orders, it does not mean that it is a case of business as usual for Christian ethics. It cannot be denied that modernisation has a significant effect on the shape of Christian ethics in the contemporary world. And it can also not be denied that in most contemporary liberal democratic societies, including South Africa, the public role of Christian ethics is restricted. Some of the challenges – and opportunities – present-day realities pose to South African churches and their members are identified and discussed.